Korelasi Profil Darah dan Komposisi Tubuh terhadap Kelembapan Kulit: Tinjauan Empiris Kelompok Dewasa di Tiga Institusi Pendidikan - Linda Yulianti; Farell Christian Gunaidi (Jurnal Kesehatan Amanah, 2025)
Background: Skin hydration is influenced by both intrinsic and systemic factors, including blood biomarkers and body composition. Physiological conditions such as anemia, dyslipidemia, and hyperuricemia are known to affect skin barrier function; however, their relationship with skin hydration has not been comprehensively studied in healthy adult populations. Objective: To analyze the association between blood parameters (hemoglobin, fasting blood glucose, uric acid, total cholesterol, HDL, LDL, and triglycerides) and body composition (visceral fat, subcutaneous fat, skeletal muscle mass) with skin hydration status (water, oil, and moisture levels) in adults. Methods: A cross-sectional study was conducted on 210 adult participants from three educational institutions in Jakarta. Data were collected through fasting venous blood analysis, bioelectrical impedance measurements, and skin analysis. Statistical analysis used Spearman correlation with a significance level of p<0.05. Results: Hemoglobin, triglycerides, and uric acid showed a significant positive correlation with skin hydration (p<0.01), while total cholesterol, LDL, HDL, and body composition parameters did not show significant associations. Fasting blood glucose was also not significantly correlated with skin moisture. Conclusion: Certain blood parameters, particularly hemoglobin, triglycerides, and uric acid, play an important role in maintaining skin hydration. These findings highlight the importance of evaluating systemic biomarkers as part of a comprehensive approach in skin care and in preventing dry skin in adult populations.